Functional neurological (conversion) symptoms mediate the effect of self-stigma in women seeking psychological help on their psychological well-being - Örüm, Dilek; Atmaca, Murad (My University, 2025)
Aim: This study aimed to examine the effect of self-stigma of seeking psychological help on psychological well-being in patients diagnosed with functional neurological symptom disorder (formerly conversion disorder) through conversion symptoms. Materials and Methods: In this cross-sectional study, the Self-Stigma of Seeking Psychological Help Scale (SSPHS), Psychological Well-Being Scale (PWBS), and Somatoform Dissociation Questionnaire (SDQ-20) were administered to the FNSD and HC groups. Results: The FNSD group consisting of 31 females (12 motor (M)-FNSD, 9 somatosensory (SS)- FNSD, and 10 mixed-FNSD) and the HC group consisting of 32 females were similar in terms of age (p = 0.350), education level (p = 0.386), marital status (p = 0.579), and working status (p = 0.136). Significant differences were observed between the FNSD and HC groups in terms of SSPHS (p<0.001), PWBS (p<0.001), and SDQ-20 (p<0.001). Significant differences were observed between the M-FNSD, SS-FNSD, and Mix-FNSD subgroups in terms of SDQ-20 (p = 0.034), SSPHS (p = 0.028), and PWBS (p = 0.015). The comparison that caused significant differences in terms of SDQ-20, SSPHS, and PWBS scores among the FNSD subgroups was between M-FNSD and Mix-FNSD. The mediating role of the FNSD symptom level (SDQ-20) in the relationship between SPH and PW was examined. The indirect effect of SPH on PW was determined as -0.436 (49.65%). The direct effect of SPH on PW was determined as -0.442 (50.35%). In the correlation analysis performed in the FNSD group, a significant relationship was found between SSPHS and SDQ-20 (r=0.921, p<0.001), between SSPHS and PWBS (r=-0.879, p<0.001), and between PWBS and SDQ-20 (r=-0.882, p<0.001). Conclusion: This study demonstrates that SPH increases and PW decreases in FNSD and that FNSD symptoms mediate the relationship between SPH and PW.
Keywords: Psychological well-being; Conversion disorder; Mediation analysis; Self-stigma; Functional neurological symptom disorder